Researching Local Wisdom “Ba’i Sighat Al Aqd” Aqd Murabahah in City of Thousand River’s: Menelisik Kearifan Lokal “ Ba’i Sighat Al Aqd” Akad Murabahah Di Kota Seribu Sungai - Hasanah, Ikhwatun; nafidzi, elman; Safitri, Dewi (UMBanjarmasin, 2021)
Everybody experienced a purchase, if a researching knowledge about purchase since of a barter system, and then thrived along with the development in implementation of Islamic Sharia. In purchase activities, Islamic regulates everything related to it, including purchase procedure. There are several things that need attention about the terms and conditions of purchase including: buyers and sellers, object of sale and purchase, sale and buying agreements. Get along in buying and selling (A Pillars of Islamic) and provisions absolutely necessary, if one of the pillars is not fulfilled, the sale and purchase is canceled. Without going through the purchase contract process, the buying and selling activity is not legal in Islam, this has become a guideline for banjar residents in buying and selling activities, the pronunciation of the qabul consent agreement is mandatory that has been practiced for generations, and without realizing it, it has become one of the local culture of the banjar community